Parallel alignment of bacteria using near-field optical force array for cell sorting - Zhao, Hai Tao (2020)
This paper presents a near-field approach to align multiple rod-shaped bacteria based on the interference pattern in silicon nano-waveguide arrays. The bacteria in the optical field will be first trapped by the gradient force and then rotated by the scattering force to the equilibrium position. In the experiment, the Shigella bacteria is rotated 90 deg and aligned to horizontal direction in 9.4 s. Meanwhile, ~150 Shigella is trapped on the surface in 5 min and 86% is aligned with angle < 5 deg. This method is a promising toolbox for the research of parallel single-cell biophysical characterization, cell-cell interaction, etc.